2021
DOI: 10.1038/s41598-021-81921-1
|View full text |Cite
|
Sign up to set email alerts
|

Higher cardiorespiratory fitness is strongly associated with lower cardiovascular risk factors in firefighters: a cross-sectional study in a German fire brigade

Abstract: Previous studies have shown significant cardiovascular risks in firefighters and that they suffer from cardiovascular events, especially on duty. Otherwise, adequate cardiorespiratory fitness is considered to have a protective effect in reducing cardiovascular complications. Therefore, the study aimed to evaluate the association between cardiorespiratory fitness and cardiovascular risks factors in firefighters. We enrolled ninety-seven male German firefighters in this cross-sectional study of cardiorespiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 37 publications
(35 reference statements)
9
49
0
1
Order By: Relevance
“…Previous studies have indicated that CRF is closely related to coronary heart disease, all-cause mortality [4,27,28], and COVID-19 mortality [29]. Individuals with high CRF levels have lower risk of dying from COVID-19, while a low CRF level is likely to increase the risk of cardiovascular disease and mortality [30,31]. For a CRF assessment, .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that CRF is closely related to coronary heart disease, all-cause mortality [4,27,28], and COVID-19 mortality [29]. Individuals with high CRF levels have lower risk of dying from COVID-19, while a low CRF level is likely to increase the risk of cardiovascular disease and mortality [30,31]. For a CRF assessment, .…”
Section: Discussionmentioning
confidence: 99%
“…ese types of strenuous working conditions cause high levels of chronic cardiovascular and physical strain, predisposing firefighters to cardiovascular disease, musculoskeletal injury, morbidity and in extreme cases, mortality [1,4,5]. Firefighters are, therefore, required to be in optimal physical conditioning to overcome many of these work-related challenges to their health [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a major challenge for the fire service and for the occupational health team is the early identification of the most susceptible workers 42 , and strategies and policies to prevent the advancement of cardiovascular disease. Recently, a study in a German Fire Service reported that firefighters with higher cardiorespiratory fitness levels had more favorable cardiovascular risk parameters, namely lower BMI, waist circumference, body fat, resting systolic blood pressure and triglycerides 43 .…”
Section: Discussionmentioning
confidence: 99%